Mangrove timber use as an ecosystem service in the Colombian Pacific (2017)
Mangroves provide ecosystem services for local communities. However, in coastal systems it is yet unknown how human settlements are directly interacting with mangroves. We assessed the use of mangroves as an ecosystem service at Málaga and Buenaventura bays, on the Colombian Pacific coast, by interviewing local communities and examining the impact of mangrove harvest on the structure of the forest, an often overlooked effect. Results showed that mangroves are mainly harvested for their wood. Rhizophora spp. are the main source of wood for fuel purposes, whereas Mora oleifera (Triana ex Hemsl.) Ducke, a mangrove associate, provides 100% of the wood used for the construction of stilt houses. The selective extraction of these species has altered the composition and structure of the forest. Sample sites undergoing harvest have relatively low densities of mangroves; however, one site at Quebrada Valencia shows signs of copious regeneration (>9000 seedlings/ha). Due to the importance of mangroves for the subsistence of coastal communities, and the threat that mangroves are exposed to in Colombia, the management of mangroves should be a priority. Managers must address the sustainability of critical species as part of conservation strategies in order to maintain ecosystem services for local communities